The role of Financial Literacy, Financial Planning on Financial Management Behavior to Improve the Performance of Car Free Day Traders in Colomadu Karanganyar - Irvina Rahma NuR Amanah; Liana Magnifera (Universitas Muhammadiyah Yogyakarta, 2023)
This research was conducted with the aim of finding out the role of financial literacy, financial planning on financial management behavior to improve the financial performance of Car Free Day traders in Colomadu Karanganyar as mediation. The method applied is using quantitative methods through primary data. Data was collected through offline surveys which were distributed to respondents and then used for statistical tests. The sample for this research is Micro, Small and Medium Enterprises that trade at Car Free Day Colomadu, Karanganyar Regency, with sampling using random sampling techniques with the number of samples used in this research being 150 respondents from traders at Car Free Day Colomadu. In this research, the tool used for analysis is the Structural Equation Model Partial Least Square (SEM-PLS) with the help of SMART PLS 3.0 software. The results of the analysis show: The results of the research show that the role of literacy has a positive and significant effect on financial behavior to improve the performance of traders in Colomadu. Financial management has a positive and significant effect on financial behavior to improve the performance of traders in Colomadu Karanganyar. Financial planning has a positive and significant effect on financial behavior to improve the performance of traders in Colomadu Karanganyar.